Analysis of storage and display frameworks based on aspect-oriented technologies - Glybovets, M.M.; Gorochovskiy, S.S.; Lysenko, І.M. (PROBLEMS IN PROGRAMMING, 2025)
A set of recommendations for the use of dependency injection and aspect-oriented programming in software development is proposed. The influence of their use on the process of design, development, testing, further support and architecture of a software product is analysed.Prombles in programming 2013; 2: 41-53